2010
DOI: 10.1002/ijc.25746
|View full text |Cite
|
Sign up to set email alerts
|

Tumor invasion induced by oxidative stress is dependent on membrane ADAM 9 protein and its secreted form

Abstract: Oxidative stress plays a role in the regulation of cancer cell metastasis which involves cell invasion and adhesion that could be supported by ADAM proteins through the activities of their metalloprotease and disintegrin domains. We hypothesized that oxidative stress could act through the induction of ADAM9 protein in some cancer cells. Indeed, Western blot analysis for ADAM9 performed on A549 cells exposed to H 2 O 2 reveals a dose-dependent induction of two proteins (80 and 68 kDa) correlated with a sharp in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Hh signaling and oxidative stress stimulate invasiveness of tumor cells2526. Cells knocked-down for Merlin showed a significant increase (p < 0.05) in their invasive potential (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Hh signaling and oxidative stress stimulate invasiveness of tumor cells2526. Cells knocked-down for Merlin showed a significant increase (p < 0.05) in their invasive potential (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…It has been suggested that oxidative mechanisms mediate the processes of drug addiction and toxicity [9,10] and that antioxidants may have therapeutic potential in managing these conditions. Little has been published on ADAMTSL3 , although the ADAM gene family has been associated with multiple diseases induced by oxidative stress [11,12]. …”
Section: Discussionmentioning
confidence: 99%
“…By preliminary experiments, LD50 and treatment times were determined to be 20 μmol/L for 48 hours for RMG‐I cells and 15 μmol/L for 24 hours for TOV21G cells. They were also treated with neutralizing anti‐human ADAM9 antibody specific to ectodomain (5 μg/mL, MAB939; R&D Systems) or non‐immune mouse IgG (5 μg/mL; BD Biosciences Pharmingen, Franklin Lakes, NJ, USA) for 1.5 hours prior to cisplatin treatment.…”
Section: Methodsmentioning
confidence: 99%